2016
DOI: 10.1097/qai.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of the ShangRing for Adult Medical Male Circumcision: Safety, Effectiveness, and Acceptability of Using 7 Versus 14 Device Sizes

Abstract: Objectives:To assess the safety, effectiveness, and acceptability of providing a reduced number of ShangRing sizes for adult voluntary medical male circumcision (VMMC) within routine service delivery in Lusaka, Zambia.Methods:We conducted a randomized controlled trial and enrolled 500 HIV-negative men aged 18–49 years at 3 clinics. Participants were randomized to 1 of 2 study arms (Standard Sizing arm vs Modified Sizing arm) in a 1:1 ratio. All 14 adult ShangRing sizes (40–26 mm inner diameter, each varying by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…All were moderate, occurred during follow-up, were considered definitely related to the circumcision, and resolved with conservative management and without sequelae. Among participants with the no-flip technique and removal at 7 days, 5.3% (6/114; 95% CI: 1.2%–9.4%) had an AE, which was not higher, using a one-sided test, than the 3% from historical data with the flip technique ( P = 0.07) 17181920213637. Following circumcision with the no-flip technique and spontaneous detachment, 1.7% (2/116; 95% CI: 0–4.1%) of participants had an AE, also not different from previously published studies ( P = 0.79).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…All were moderate, occurred during follow-up, were considered definitely related to the circumcision, and resolved with conservative management and without sequelae. Among participants with the no-flip technique and removal at 7 days, 5.3% (6/114; 95% CI: 1.2%–9.4%) had an AE, which was not higher, using a one-sided test, than the 3% from historical data with the flip technique ( P = 0.07) 17181920213637. Following circumcision with the no-flip technique and spontaneous detachment, 1.7% (2/116; 95% CI: 0–4.1%) of participants had an AE, also not different from previously published studies ( P = 0.79).…”
Section: Resultsmentioning
confidence: 87%
“…The no-flip technique simplifies the procedure since eversion of the foreskin and making 8–10 small slits needed in the tissue that remains after the foreskin is excised is unnecessary. Results from a study in Zambia showed that reducing the number of adult device sizes in half (from 14 to 7) by eliminating every other size did not reduce the safety, effectiveness, or acceptability of ShangRing VMMC 37. Having to stock fewer sizes would simplify supply chain logistics and inventory issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good outcomes are also seen with delivery of services in mobile units, which will allow programs to extend reach to more remote areas. 23 , 24 …”
Section: Safetymentioning
confidence: 99%